Students’ Perceptions on Writing Activities by Using Padlet Application - Suryani, Irma; Daulay, Sholihatul Hamidah (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2022)
The purpose of this research determined students’ perception of the use of the Padlet application through writing class activities. Padlet is a learning tool of technology in the Industrial revolution 4.0 and the education sector to make the learning process more interesting. Padlet is a free web-based app that offers a “wall” that allows users to post words, photographs, and clips that anyone with the link or address to the particular wall can view, and the web allows you to create a virtual wall. It also has become popular since one of the applications which have supported teaching and learning activities in and out of the classroom. The study applied a qualitative research design. The data was collected through observation and interviews with 30 students of Junior High School in Medan. Based on the researcher‘s interview, all of the data was analyzed descriptively to describe students‘ perspectives. The researcher offers some questions from the interview questionnaire that pertain to the use of Padlet through writing class. The research’s finding is based on the student’s positive perceptions towards using Padlet, students agreed that accessing and using Padlet is simple than traditional writing activities, in writing practices Padlet is appealing due to its features, and using Padlet for writing practice is more enjoyable, and improve their writing skill in the learning process and with Padlet can develop their creativity in writing class. The implication of padlet in writing activity is the students experienced increased beneficial outcomes.